Dried Clove Leaf as Corrosion Inhibitor for Medium Carbon Steel in Acidic Media - Rosidah, Afira Ainur; Roni, Kiki Ridho Syah; Yunus, Muhammad (Journal of Mechanical Engineering, Science, and Innovation, 2023)
Medium carbon steel is a widely used steel variant known for its susceptibility to mechanical property degradation due to corrosion. In order to decrease the corrosion rate of medium carbon steel, various protective measures are employed such as the addition of inhibitors. Dried Clove Leaf (DCL) extract was extracted and applied as an inhibitor for medium carbon steel AISI 1040 in different acidic environments. Fourier-transform infrared spectroscopy (FTIR) was conducted to analyze the compounds present in the clove leaf extract. Subsequently, corrosion rate and inhibitor efficiency were assessed to demonstrate the effectiveness of the clove leaf inhibitor. The parameters under this research included varying inhibitor concentrations for 0%, 5%, 10%, 15%, and acidic media using HCl and H2SO4. The successful extraction of DCL was confirmed by the presence of a C=C bond in the FTIR results, occurring at wavenumbers ranging from 1638 to 1514 cm-1, indicative of the presence of benzene rings corresponding to eugenol (a phenolic component). The inhibitor exhibited remarkable efficiency, reaching its peak at 96.51% when used with HCl media at a DCL concentration of 15%. This high efficiency is notably reflected in the significant reduction of the corrosion rate from 352.96 mpy to 12.31 mpy in the presence of HCl media.